The effects of the serotonin transporter polymorphism and age on frontal white matter integrity in healthy adult women - Jonassen, Rune; Endestad, Tor; Neumeister, Alexander; Foss Haug, Kari Bente; Berg, Jens Petter; Landro, Nils I. (Frontiers in Human Neuroscience, 2012)
Studies of populations at genetic risk have the potential to explore the underlying structural and functional mechanisms in the development of psychological disorders. The polymorphic region (5-HTTLPR) in the serotonin transporter gene (SLC6A4) has been associated with major depression (Caspi et al., 2003). In healthy women, variation in the human brain white matter microstructure integrity in the uncinate fascicule (UF) has been suggested as an endophenotypes in the development of major depression (MDD). Pacheco et al. (2009) found a unique effect of age and 5-HTTLPR within the left frontal UF. The present study examined whether these associations persist along the adult life span. Thirty-seven right-handed healthy women between 21 and 61 years of age were invited for a diffusion MRI study. The functional polymorphism 5-HTTLPR located in the promoter region of the SLC6A4 gene was genotyped using polymerase chain reaction (PCR). Fractional anisotropy (FA) was generated for the UF based on Tract-Based Spatial Statistics (TBSS). Models of emotion regulation circuitry suggest that working memory is important in conscious emotion regulation (Price and Drevets, 2010). To explore if 5-HTTLPR is related to this aspects of emotion processing, a working memory pathway, the superior longitudinal fascicule (SLF) was included. The results demonstrate that age may explain the hypothesized association between 5-HTTLPR and frontal uncinate fascicule white matter integrity in healthy adult women. Both white matter changes associated with the aging process and those associated with growth and development may explain why the earlier reported unique effects of genotype in frontal UF FA do not persist into adulthood.